Potential Role of APEX1 During Ferroptosis - Guo, Nan; Chen, Yan; Zhang, Yuhong; Deng, Yonghao; Zeng, Fancai; Li, Xiang (Frontiers in Oncology, 2022)
Ferroptosis is a recently discovered category of programmed cell death. It is much different from other types of cell death such as apoptosis, necrosis and autophagy. The main pathological feature of ferroptosis is the accumulation of iron-dependent lipid peroxidation. The typical changes in the morphological features of ferroptosis include cell volume shrinkage and increased mitochondrial membrane area. The mechanisms of ferroptosis may be mainly related to lipid peroxidation accumulation, imbalance in amino acid antioxidant system, and disturbance of iron metabolism. Besides, hypoxia-inducible factor (HIF), nuclear factor-E2-related factor 2 (Nrf2), and p53 pathway have been demonstrated to be involved in ferroptosis. At present, the molecular mechanisms of ferroptosis pathway are still unmapped. In this review, an outlook has been put forward about the crucial role of apurinic/apyrimidinic endodeoxyribonuclease 1 (APEX1) in the regulation of ferroptosis. APEX1 plays an important role in the regulation of intracellular redox balance and can be used as a potential inhibitor of ferroptotic cell death. Bioinformatics analysis indicated that the mRNA level of APEX1 is decreased in cases of ferroptosis triggered by erastin. Besides, it was found that there was a significant correlation between APEX1 and genes in the ferroptosis pathway. We have discussed the possibility to employ APEX1 inducers or inhibitors in the regulation of ferroptosis as a new strategy for the treatment of various human diseases.